Analisis Strategi Bisnis MM Bakery Madiun Di Masa Pandemi Covid-19 - Pratiwi, Arum Nanda; Wahyudi Utomo, Supri; Astuti, Elly (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2022)
This study aims to identify what business strategies should be implemented by UMKM Bakery in Madiun during the COVID-19 pandemic. The research method used is descriptive qualitative research. Primary data sources. Data collection techniques are observation, interviews, and documentation. The data analysis used in this research is data reduction, data display, and conclusion drawing/verification. The results of this study are the results of the analysis of internal and external factors through the calculation of the IFE matrix and the EFE matrix with the results of each having a total score of 2.96 and 3.12. Then the mapping is done through the IE matrix which shows that the position of MM Bakery is in cell II, namely growing and building. So the right strategy to be applied during the current pandemic is product development.